Family location and caregiving patterns from an international perspective - Helmut Rainer; Thomas Siedler (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper conducts a cross-national econometric analysis of intra-family location and caregiving patterns. First, we assess, from an international perspective, the relationship between family structure and the geographic proximity between adult children and their parents. We then examine whether differences in family structure affect the amount of informal care adult children provide to their elderly parents. Lastly, we look for cross-country differences in family location and caregiving patterns, and interpret observed differences in terms of heterogenous institutional solutions to the long-term care problem. Our results not only provide a new empirical perspective on the geography of the family, but also give interesting insights into how family-related and institutional factors shape patterns of time transfers from adult children to elderly parents.
Keywords: D19; J14; 330; geography of the family; child-to-parent time transfers; Familiensoziologie; Räumliche Verteilung; Familienpflege; Kinder; Eltern; Entfernung; Schätzung; Welt